Study on Magnetic Properties Characterization of Aceh Iron Sand as Raw Biomedical Application Materials - Sayuti, Muhammad; Yusuf, Muhammad; Putra, Reza; Wirawan, Riza (International Journal of Engineering, Science and Information Technology, 2025)
The magnetic properties characterization of Aceh iron sand as the preferred material for biomedical applications was studied. Meanwhile, Aceh's iron sand is used as raw cement-making material. It is hoped that in the future, it can be used in many different biological and medical applications, such as diagnostic tests for early disease detection, to serve as tools for non-invasive imaging and drug development. Samples of the natural resource were prepared using a magnetic separator, and the concentrates were mashed by the ball milling method to achieve 112.7µm (MK), 119.3 µm (MT), 112,4 µm (LP), and 115.1 µm (SK) particle size. These features were evaluated from loop hysteresis using a vibration sample magnetometer (VSM), while x-ray diffraction (XRD) was employed to analyze iron oxide. The results estimated the values of saturation magnetization, remanent magnetization, and coercivity from Mon Klayu, Mantak Tari, Lam Panah, and Syiah Kuala at 67.79 emu/g, 10.36 emu/g and 0.02 T; 83.49 emu/g, 13.22 emu/g and 0.02 T; 62.17 emu/g, 9.32 emu/g and 0.02 T; 73.26 emu/g, 10.34 emu/g and 0.02 T, respectively. However, Fe3O4 (magnetite) occurred predominantly in the selected locations.